An inorganic–organic hybrid supramolecular framework as a high-performance anode for lithium-ion batteries. Issue 15 (26th March 2018) - Xia, Shubiao; Li, Fushao; Li, Xue; Cheng, Feixiang; Sun, Chengke; Liu, Jian-Jun; Guo, Hong
Abstract : We achieved an excellent anode for a lithium-ion battery for the first time based on an inorganic–organic hybrid supramolecular nanotube. Abstract : Herein, an excellent anode was achieved for a lithium-ion battery based on a polyoxometalate-organic framework [Ni5 (OH)3 (trzS)3 (en)(H2 O)(B-α-PW9 O34 )] for the first time. It can deliver a capacity of 710 mA h g −1 at 100 mA g −1 after 50 cycles and a high capacity retention of 82.2% after 500 cycles at a high rate of 800 mA g −1, which is supposed to be due to the unique porous characteristic and high chemical stability of the proposed anode. The higher capacity was ascribed to Ni and W of the building unit taking part in lithium storage.